Differential Regulation of Syngap1 Translation by FMRP Modulates eEF2 Mediated Response on NMDAR Activity - Paul, Abhik; Nawalpuri, Bharti; Shah, Devanshi; Sateesh, Shruthi; Muddashetty, Ravi S.; Clement, James P. (Frontiers in Molecular Neuroscience, 2019)
SYNGAP1, a Synaptic Ras-GTPase activating protein, regulates synapse maturation during a critical developmental window. Heterozygous mutation in SYNGAP1 (SYNGAP1+/-) has been shown to cause Intellectual Disability (ID) in children. Recent studies have provided evidence for altered neuronal protein synthesis in a mouse model of Syngap1+/-. However, the molecular mechanism behind the same is unclear. Here, we report the reduced expression of a known translation regulator, FMRP, during a specific developmental period in Syngap1+/- mice. Our results demonstrated that FMRP interacts with and regulates the translation of Syngap1 mRNA. We further show that, during development, reduced translation, and subsequent decrease in FMRP level leads to a compensatory increase of Syngap1 translation in Syngap1+/-. These developmental changes are reflected in the altered response of eEF2 phosphorylation downstream of NMDA Receptor (NMDAR)-mediated signalling. In this study, we propose a cross-talk between FMRP and SYNGAP1-mediated signalling which can also explain the compensatory effect of impaired signalling observed in Syngap1+/- mice.